HUBUNGAN PERHATIAN INTENSIF GURU TERHADAP MOTIVASI ESKTRINSIK SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA N 5 SELUMA - Nelly Marhayati; Pasmah Chandra; Yemi Heprianti (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Student learning motivation is not only obtained from the support and attention of parents but also from teachers at the School. Based on this the purpose of this study was to determine the relationship of teacher attention to student motivation. This study is a correlation study whose data analysis uses product moment analysis. Performed on 105 students of class X from SMAN 05 Seluma. The results showed that a rxy value of 0.812 was obtained between 0.800 to 1,000. Based on these results it can be said that the correlation between variables X and Y is classified as very strong. This proves that there is a positive relationship between teacher support for student motivation.